Desenvolvimento de um módulo I/O sem fio para uso com CLP’S - Paixão, Gustavo Ezequiel da (2014)
In this project to develop a couple of in and out digital modules(I/O), that will be used to receive and send information to the peripheries that are at a certain distance from a logical programmed controller (CLP), with the need of cables. An in module was developed (for sensors, bottoms, end of course key) and the out module (to act relays, valves, pneumatic commands and CLP entrances). The development of this couple of modules brings benefits to the industry application and general automation, because it`s possible to increase the flexibility and the installations time saving. In order for this development to happen a CLPs from LS Industrial (LSIS) Systems was used, Sick sensors and other external accessories, to validate the modules. We chose to use the LSIS`CLP, because this is a consolidated brand in Asia, especially in South Korea and also because the Program Software is free. The main component used in to make the module I/O is the XBee, which is the responsible one for the signals transmission between the modules and has characteristics that guarantee a great stability and reliability in the applications in which they were used.